Responses of Dry Matter Digestibility, Organic Matter Digestibility, Gas Production, and Methane Emission of Rice Straw to Ammoniation-Fermentation Methods and Fermentation Duration - Koji Al Adam; Hendra Koesmara; Diah Fridayati; Muhammad Ammar; Said Mirza Pratama (Livestock and Animal Research, 2026)
This study aimed to evaluate the effect of Amofer methods and fermentation duration on the nutritional quality, digestibility, and methane production of rice straw. Two Amofer methods were compared: direct (A1) and indirect (A2), combined with four fermentation periods (0, 7, 14, and 21 days). The results showed that both factors significantly affected dry matter digestibility (DMD), organic matter digestibility (OMD), and gas production (P<0.05). The indirect Amofer method (A2), which involved ammoniation prior to microbial fermentation, produced higher DMD (43.10%) and OMD (44.52%) than the direct method (A1). The best results were obtained from A2B2 (indirect Amofer, 14 days), with the highest DMD (55.96%) and OMD (59.37%), as well as efficient gas production (103.7 mL/g DM) and lower methane emission (1.48 mL CH₄/g DM). Improved digestibility under A2B2 was associated with the breakdown of lignocellulosic bonds during ammoniation and enhanced microbial activity during fermentation. In contrast, extended fermentation (21 days) decreased digestibility and increased methane output. These findings indicate that the indirect Amofer method with 14 days of fermentation optimizes rice straw utilization by enhancing feed digestibility, stimulating rumen microbial efficiency, and reducing methane emissions, contributing to sustainable ruminant nutrition systems.